Effect of extraction solvents and drying conditions on total phenolic content and antioxidant properties of watermelon rind powder - Ho, Lee-Hoon; Nor Fadhilah Ramli; Tan, Thuan-Chew; Norlia Muhamad; Mohd Nizam Haron (Penerbit Universiti Kebangsaan Malaysia, 2018)
The objective of the present study was to determine the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant properties, i.e. 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and ferric reducing antioxidant potential (FRAP) assay, of red- and yellow-fleshed watermelon rind powders prepared using different drying conditions (hot-air oven drying at 40 and 60°C and freeze drying). All the samples were subjected to four different solvent extract using water, methanol, ethanol and acetone prior analyses. Water extract from red- and yellow-fleshed watermelon rind powders presented highest value for TPC and TFC. However, methanol extract samples showed highest value for antioxidant properties (DPPH and FRAP) followed by acetone, ethanol and water extract. By comparing the drying conditions, all samples dried using hot-air dryer at 40 and 60°C had significantly higher (p<0.05) in TPC value than the samples dried using freeze dryer. However, samples dried using freeze dryer showed highest in DPPH and FRAP values. The present obtained results would be useful to the food and pharmaceutical industries for developing of functional ingredients.